Sex hormones alter the effect of aspirin on bleeding - Aftab, Muhammad Tariq; Shakeel, Saba; Tariq, Hira; Shaikh, Saeed (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Interaction of aspirin and sex hormones was investigated through bleeding time. Methods: Bleeding time in 32 males and 105 unmarried females with previous 6 normal menstrual cycles and all aged between 18 to 21 years was found by Duke’s method before and after 2 hours of aspirin administration. Phase of menstrual cycle of each female was determined by present menstrual history. Results: Bleeding time in 32 male was 69.33± 4.94 seconds and in 105 female was 73.03±1.89 seconds which were not statistically different (P>0.05).This time was increased to 107.66±4.76 seconds in males and 113.65±3.73 seconds in females after aspirin administration which were statistically different (P<0.05). The response in males was relatively greater (P<0.0005) as compared to females (P<0.0025). Among females, 44 were in follicular phase while 29 were in luteal phase as per their menstrual histories. Bleeding time in females in Follicular phase was increased from 70.22±2.90 seconds to 109.65±3.82 seconds and in females in luteal phase from 81.13±4.26 seconds to 117.95±7.49 after aspirin administration. The statistics of bleeding time in follicular and luteal Phases shows a statistically significant (P<0.05) difference before aspirin but non-significant (P>0.05) difference after aspirin administration with a greater effect in Follicular phase probably due to estradiol. Conclusion: Males respond to aspirin more as compared to females which is likely the effect of the drug and testosterone interaction. Similarly females in the follicular phase respond to aspirin more as compared to females in the luteal phase which may be a result of interaction of estrogen and aspirin.